Grip strength and the metabolic syndrome: findings from the Hertfordshire Cohort Study. - Sayer, A; Syddall, H; Dennison, E; Martin, H; Phillips, D; Cooper, C; Byrne, C (2007)
INTRODUCTION: Sarcopenia, the loss of muscle mass and strength with age, is significantly associated with type 2 diabetes in older people. AIM: To determine whether there is a relationship between grip strength and features of the metabolic syndrome. DESIGN: Cross-sectional study. METHODS: Data were collected on grip strength, fasting glucose, triglycerides and HDL cholesterol, blood pressure, waist circumference and 2 h glucose after an oral glucose tolerance test, in a population-based sample of 2677 men and women aged 59-73 years. RESULTS: In men and women combined, a standard deviation (SD) decrease in grip strength was significantly associated with higher: fasting triglycerides (0.05 SD unit increase, 95%CI 0.02-0.09, p = 0.006); blood pressure (OR 1.13, 95%CI 1.04-1.24, p = 0.004); waist circumference (0.08 SD unit increase, 95%CI 0.06-0.10, p < 0.001); 2 h glucose (0.07 SD unit increase, 95%CI 0.03-0.11, p = 0.001) and HOMA resistance (0.05 SD unit increase, 95%CI 0.01-0.09, p = 0.008), after adjustment for gender, weight, age, walking speed, social class, smoking habit and alcohol intake. Lower grip strength was also significantly associated with increased odds of having the metabolic syndrome according to both the ATPIII (OR 1.18, 95%CI 1.07-1.30, p < 0.001) and IDF definitions (OR 1.11, 95%CI 1.01-1.22, p = 0.03). DISCUSSION: Our findings suggest that impaired grip strength is associated with the individual features, as well as with the overall summary definitions, of the metabolic syndrome. The potential for grip strength to be used in the clinical setting needs to be explored.